Managing small business : an entrepreneurial emphasis - Petty, J. William; Palich, Leslie E. ;Hoy, Francis;Longenecker, Justin G. ([Australia] : South-Western, 2012)
Its aim is to provide instruction and guidance that will greatly improve your odds for success towards its own entrepreneurial journey.
PART 1: Entrepreneurship: a world of opportunity - 1. The entrepreneurial life -- 2. Integrity and ethics of entrepreneurship -- PART 2: Starting from scratch or joining an existing business -- 3. Starting the business -- 4. Franchises and buyouts -- 5. The family business -- PART 3: Developing the new venture business plan -- 6. Creating business plans -- 7. The marketing plan -- 8. The organization of the business -- 9. The location plan -- 10. Financial statements -- 11. Projecting financial requirements -- 12. A firm's sources of financing -- 13. The harvest plan -- PART 4: Focusing on the customer: marketing growth strategies -- 14. Customer relationships -- 15. Product and supply chain management -- 16. Pricing and credit -- 17. Promotional planning -- 18. Global marketing -- PART 5: Managing growth in the small business -- 19. Professional management and leadership -- 20. Human resource management -- 21. Operations management -- 22. Managing the firm's assets -- 23. Risk management -- Cases -- Appendix A: Sample business plan -- Appendix B: Valuing a business
Includes bibliographical references and index.
Keywords: SMALL BUSINESS - MANAGEMENT